The Afghan water law: a legal solution foreign to reality? - Wegerich, Kai (Informa UK Limited, 2010)
In this article the suggested permit and license systems included in the draft Afghan Water Law of 2008 (superseding those laws of 1981 and 1991) are examined by comparing them with main canal data from two pilot studies within the Kunduz Basin. The comparison highlights the difficulty of making these proposed legal frameworks operative. Overall, it appears that the sections within the law on permits and licenses are not implementable within or even useful for the traditional irrigation systems, but mainly play into the hands of the national hydrocracy and please international donors.